Jahresbericht 1998 Annual Report : Magazin [3]. - Amanshauser, Hildegund; Dusini, Matthias; Eichhorn, Maria; Frisinghelli, Christine; Janda, Martin; Kladler, Kurt; Krön, Peter; Matzer, Ulrike; Pumhösl, Florian; Rainer, Cosima; Reinert, Ulrike; Vogel, Sabine B.; et al. (Salzburg : Salzburger Kunstverein, 1998)
Eichhorn, Maria ; Pumhösl, Florian ; Douglas, Stan ; Bond, Eleanor ; Hoedt, Ralf ; Zoitl, Moira ; Fischbacher, Gertrud ; Deleu, Luc ; Huber, Dieter ; Kuss, Kai ; Siekmann, Andreas ; Skene, Cathy ; Spring, Gerhard
Biografie
Duits & Engels
boek